2017
DOI: 10.3389/fmars.2017.00247
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Acclimation to Iron Limitation Reveals New Insights in Metabolism Regulation of Synechococcus sp. PCC7002

Abstract: In large areas of the ocean phytoplankton growth is limited by the scarcity of iron (Fe), an essential co-factor for multiple enzymes. Phytoplankton has hence developed strategies to survive under Fe limitation. Here, we characterize the response to Fe limitation of the cyanobacterium Synechococcus sp. PCC7002 acclimated to different Fe concentrations in chemically characterized synthetic seawater. The inorganic Fe concentrations used represent levels of Fe limitation relevant for different domains of the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 74 publications
2
24
0
Order By: Relevance
“…PCC7002 under increasing severity of Fe limitation (Blanco‐Ameijeiras et al . ) have demonstrated that their expression profile did not follow a linear increase proportional to the severity of Fe limitation (Fig. b).…”
Section: Factors Preventing the Bioreporter From Giving A Monotonic Dmentioning
confidence: 93%
See 4 more Smart Citations
“…PCC7002 under increasing severity of Fe limitation (Blanco‐Ameijeiras et al . ) have demonstrated that their expression profile did not follow a linear increase proportional to the severity of Fe limitation (Fig. b).…”
Section: Factors Preventing the Bioreporter From Giving A Monotonic Dmentioning
confidence: 93%
“…PCC7002 acclimated to increasing severity of Fe limitation highlighted the importance of long‐term acclimation processes and showed contrasting strategies with respect to those previously reported under sudden Fe starvation (Blanco‐Ameijeiras et al . ). In previous work from Boyanapalli et al .…”
Section: Optimization Of Bioreporter Responsementioning
confidence: 97%
See 3 more Smart Citations